The impact of the COVID-19 pandemic on the employment situation and financial well-being of families with children in Austria: Evidence from the first ten months of the crisis - Nadia Steiber; Christina Siegert; Stefan Vogtenhuber (Journal of Family Research, 2021)
Objective: This study investigates the impact of the COVID-19 pandemic on the employment situation of parents and in turn on the subjective financial well-being of families with children in Austria.